A peculiar association: the skin and the subcutaneus diverticula of the Southern Screamer (Chauna torquata, Anseriformes) - Picasso, Mariana Beatriz Julieta (2014)
The aim of this work is to describe for the first time the skin and the subcutaneous diverticula at histological level (by light microscopy) of the Southern Screamer Chauna torquata. We found that the main distinguishing features of the skin were the presence of deep and branched epidermal invaginations whereas in the dermis abundant elastic fibers were found. These skin features could provide a great stretchability to the skin which, in turn, are related to the change of volume that may experience the subcutaneous diverticula.. Since screamers are flying birds that soar to great heights, the presence of subcutaneous diverticula together with another anatomical features (like a great skeletal pneumaticity) could favor a body mass reduction and an optimization in its mode of locomotion.